PERLINDUNGAN HUKUM ATAS HAK POLITIK PEREMPUAN OLEH NEGARA - Daku, Yosefina (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 2 (2015)DO - 10.24843/JMHU.2015.v04.i02.p10, 2015)
As the law states , Indonesia  provide the protection of the rights for of all people without the discrimination. By the basis of the mandate of the Preamble to the Constitution of 1945 that " a just and civilized humanity," the Indonesian state guarantees of a society that is fair. Political rights granted by the country with regard to discrimination is legal protection by the state against women's political rights. By participating in the convention and recognized in the form of Law Number 7 Y ear of 198 4 on Ratification of the Convention on the Elimination of All Forms of Discrimination Against Women , an attempt by the state to remove the problems in realizing the equality of women and men. Therefore  the  problem  that  can  formulated are: 1) how the legal protection of women's political rights in Indonesia? 2) how the implementation of Law N umber 7 Y ear of 1984 on Ratification of the Convention on the Eliminationof All Forms of Discrimination Against Women Related Political Rights of Women?. The purpose of this study was to examine the legal protection by the state against the ful fillment of women's political rights in Indonesia and the implementation of protection of women's political rights pursuant of Law Number7 Y ear of 1984. This research is a normative law . The technique used in this research is to use the concept approach and statutory approach to reviewing the legislations and legal literatures. Rights protection as a form of justice for each person more specifically regulated in Law about Human Rights . Protection of the rights granted to women by the state including the protection of the political field regulated in some provisions of other legislation. By removing discrimination against women in it’s implementation still look at the culture and customs which is certainly not easy to do and the state is obliged to realize the objectives of the convention
Keywords: Responsibility of States, CEDAW, Legal Protection, Women' s Political Rights